2011
DOI: 10.2903/sp.efsa.2011.en-187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between 3‐MCPD and its palmitic esters in a 90‐day toxicological study

Abstract: A 90-day toxicological study was carried out administering equimolar doses of either 3-MCPD (respectively 29.5, 7.37, and 1.84 mg/kg b.w. per day) or 3-MCPD dipalmitate (respectively 156.75, 39.19, and 9.78 mg/kg b.w. per day) to both male and female rats (10 animals per group). Urinary 3-MCPD and 3-MCPD mercapturate were used to monitor exposure to both 3-MCPD and its dipalmitate, and to assess the bioavailability of the latter (equimolar doses of dipalmitate gave rise to urinary metabolites lower by 30 % as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 15 publications
(14 reference statements)
5
76
4
2
Order By: Relevance
“…Whereas the toxicological properties of 3-MCPD have been extensively studied in the past decades, only few studies were conducted to examine the toxicological properties of 3-MCPD fatty acid esters so far. Histopathological examination has confirmed that kidney is also the critical organ for 3-MCPD ester, but the observed changes after treatment with 3-MCPD dipalmitate in a 90-day oral rat study were slighter in comparison with equimolar 3-MCPD treatment (Barocelli et al 2011). A more recent oral 13-week study with rats revealed similar subchronic toxic effects of 3-MCPD fatty acid esters in comparison with free 3-MCPD (Onami et al 2014b).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Whereas the toxicological properties of 3-MCPD have been extensively studied in the past decades, only few studies were conducted to examine the toxicological properties of 3-MCPD fatty acid esters so far. Histopathological examination has confirmed that kidney is also the critical organ for 3-MCPD ester, but the observed changes after treatment with 3-MCPD dipalmitate in a 90-day oral rat study were slighter in comparison with equimolar 3-MCPD treatment (Barocelli et al 2011). A more recent oral 13-week study with rats revealed similar subchronic toxic effects of 3-MCPD fatty acid esters in comparison with free 3-MCPD (Onami et al 2014b).…”
Section: Introductionmentioning
confidence: 57%
“…per day 3-MCPD dipalmitate or 7.37 mg/kg b.w. per day 3-MCPD) (Barocelli et al 2011). In another study, Wistar rats were treated with 12.3 mg/kg b.w.…”
Section: Namesmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicological data on 3-MCPD esters are scarce. A sub-chronic toxicity study in rats administered equimolar doses of free 3-MCPD or a di-ester (di-palmitate) via gavage confirmed that the kidneys and testes are the main target organs for 3-MCPD toxicity as well as for the 3-MCPD di-ester studied, although the effects were milder and proportional to the urinary excretion of metabolites, which was lower than that observed for free 3-MCPD (Barocelli et al, 2011). Benchmark doses for renal and testicular damage were higher for the di-ester compared to those calculated for 3-MCPD, probably due to a slower and/or lower bioavailability and excretion rate (Barocelli et al, 2011).…”
Section: Context Of the Scientific Outputmentioning
confidence: 81%
“…Recently, a few studies (Barocelli et al 2011;Liu et al 2012;Tee et al 2011) had evaluated toxicological properties of 3-MCPD esters using in vitro and in vivo approaches and confirmed the oral toxicity and cytotoxicity of 3-MCPD mono-and di-fatty acid esters. Studies showed the occurrence of 3-MCPD-esters in fatty food stuffs (Doležal et al 2005;Hamlet and Sadd 2004;Zelinková et al 2009;Zelinková et al 2006), even in human breast milk (Zelinková et al 2008).…”
mentioning
confidence: 89%